A comparative study of body size evolution in moths: evidence of correlated evolution with feeding and phenology-related traits - Foerster, Stênio Ítalo Araújo; Clarke, John T; Õunap, Erki; Teder, Tiit; Tammaru, Toomas (Journal of evolutionary biology, 2024)
Interspecific variation in body size is one of the most popular topics in comparative studies. Despite recent advances, little is known about the patterns and processes behind the evolution of body size in insects. Here, we used a robust data set comprising all geometrid moth species occurring in Northern Europe to examine the evolutionary associations involving body size and several life-history traits under an explicitly phylogenetic framework. We provided new insights into the interactive effects of life-history traits on body size and evidence of correlated evolution. We further established the sequence of trait evolution linking body size with the life-history traits correlated with it. We found that most (but not all) of the studied life-history traits, to some extent, influenced interspecific variation in body size, but interactive effects were uncommon. Both bi- and multivariate phylogenetic analyses indicated that larger species tend to be nocturnal flyers, overwinter in the larval stage, feed on the foliage of trees rather than herbs, and have a generalist feeding behaviour. We found evidence of correlated evolution involving body size with overwintering stage, host-plant growth form, and dietary specialization. The examination of evolutionary transitions within the correlated evolution models signalled that overwintering as larvae commonly preceded the evolution of large sizes, as did feeding on tree foliage and the generalist feeding behaviour. By showing that both body size and all life-history traits correlated with it evolve at very slow rates, we caution against uncritical attempts to propose causal explanations for respective associations based on contemporary ecological settings.
Keywords: Animals; velikost těla; můry; Life History Traits; body size; biologická evoluce; evolution; stravovací zvyklosti; Body Size; Moths; Phylogeny; evolutionary ecology; Feeding Behavior; zvláštnosti životní historie; macroevolution; zvířata; Biological Evolution; fylogeneze; insects